Uniform Convergence of Spectral Expansions in the Terms of Root Functions of a Spectral Problem for the Equation of a Vibrating Beam (Journal of Mathematical Study, 2021)
In this paper we consider a spectral problem which describes bending vibrations of a homogeneous rod, in cross-sections of which the longitudinal force acts,the left end of which is fixed rigidly and on the right end is concentrated an elasticallyfixed load. We study the uniform convergence of spectral expansions in terms of rootfunctions of this problem.